2017
DOI: 10.11002/kjfp.2017.24.3.413
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-inflammatory activity of extracts from red beet (Beta vulagaris) root

Abstract: This study was designed to examine the in vitro antioxidant and anti-inflammatory effects of red beet (Beta vulagaris) root. Red beet root was extracted using 70% ethanol and then fractionated sequentially with n-hexane, ethyl acetate and butanol. Antioxidative ability was evaluated by bioassays using total polyphenol contents and ABTS (2,2'-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid diammonium salt) radical scavenging activity. Ethyl acetate fraction of red beet root was best on total polyphenol conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“…2A. In a previous study, it was reported that the NO production inhibition effect through iNOS expression inhibition was greater than that of the red beetroot extract by COX-2 inhibition of PGE2 synthesis could be confirmed (Yi et al, 2017).…”
Section: Inhibitory Effect Of B Tinctoria Root Extract Treatment On N...mentioning
confidence: 75%
“…2A. In a previous study, it was reported that the NO production inhibition effect through iNOS expression inhibition was greater than that of the red beetroot extract by COX-2 inhibition of PGE2 synthesis could be confirmed (Yi et al, 2017).…”
Section: Inhibitory Effect Of B Tinctoria Root Extract Treatment On N...mentioning
confidence: 75%
“…Interest in adverse substances with environmentally friendly functions is increasing [ 45 ]. Recently, studies on disease treatment and prevention using natural products and the development of health-functional materials have been actively conducted [ 46 ]. Therefore, the viability of natural antioxidants is evaluated by measuring antioxidant compounds and their activity.…”
Section: Discussionmentioning
confidence: 99%
“…비트(Beta vularis L.)는 유럽 남부 및 지중해 연안이 원 산지로 쌍떡잎식물강 명아주과(Chenopodiceae)의 두해살이 풀이다. 비트는 칼로리가 낮고 각종 미네랄과 비타민이 풍부 하여 다양하게 건강상의 유익함을 줄 수 있는 식물이다 (Yi et al, 2017). 작물의 내염성(saline tolerant)은 식물이 생육하는 배지에서 과도한 염의 영향을 견딜 수 있는 식물의 능력이다.…”
Section: 서 론unclassified